Couples education via videoconferencing: bridging the demand gap - Kysely, Andrea (Curtin University, 2015)
The Australian study is the first to provide evidence for couples intervention via videoconferencing as a viable alternative to face-to-face. Thirty couples were randomly assigned to either a face-to-face, or videoconferencing condition, and completed a couples behavioural education program. Through qualitative analysis several themes were identified, reflecting open-mindedness, acceptance, satisfaction, and the establishment of a strong working alliance. Statistical analysis further supported these finding, showing no significant effect of the technology, and positive clinical outcomes.